(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Psychology is especially utilized. It attempts to examine the child’s educational behaviour andimplements the psychological understanding in education. Judd analyses and explains the changes inpeople through different phases of the development from infancy to adulthood. Educational psychology isthe science. Educational psychology apparently addresses different learning and teaching issues. This iswhy psychology of education is called as Teaching and learning psychology.